Creep of the Ti₃AlC₂ MAX-phase ceramics - Boyko, Yu.I.; Bogdanov, V.V.; Gevorkyan, E.S.; Vovk, R.V.; Korshak, V.F.; Kolesnichenko, V.A. (Functional Materials, 2019)
The process of plastic deformation of multicomponent ceramics based on the MAX phase at room temperature and at higher (1000 °C) temperature has been studied by dilatometry and microindentation. Based on the experimentally obtained dependence of the strain rate of the material on the magnitude of the applied load, conclusions were made about the mechanisms controlling the plastic deformation process in the samples under study.